Effect of World Oil Prices on Cryptocurrency Return - Mohd. Heikal; Maulana Majied Sumatrani Saragih; Rico Nur Ilham; Muammar Khaddafi; Rusydi Rusydi (PT. Radja Intercontinental Publishing, 2022)
This study aims to determine the effect ofWorld Oil Priceseffect on Return Cryptocurrency. The researcher uses a descriptive quantitative approach. Replication research is the repetition of the basic experiment. The analytical method used is multiple linear regression model. As for the results of this study, the variable World Oil Price (X) can explain the Return Cryptocurrency variable (Y) of 27.9%.variableWorld Oil Prices(X) significant effectagainst the Return Cryptocurrency variable (Y). Oil price fluctuations on the world market have an effect on Cryptocurrency Return. In this study, it is found that fluctuations in oil prices in the world market have a positive impact on Cryptocurrency Return. That is, the increase in oil prices encourages the rise of Cryptocurrencies. Researchers suggest to pay more attention to world oil prices first before other commodities, because the impact of world oil prices is very large on commodity prices worldwide. So, for example, a decline in world oil prices can affect Cryptocurrency Return.